A corpus-based archive of learner english in Sabah/Sarawak (Cales Phase 2) / Simon Botley@ Faizal Hakim ... [et al.] - Hakim, Botley @ Faizal; Metom, Lilly; Dillah, Doreen (2007)
This report describes the second phase of the learner corpus project called CALES (Corpus-based Archive of Learner English in Sarawak). The original project collected 89,000 words of learner writing in the form of argumentative essays written by students taking English proficiency courses in UiTM’s Sarawak Branch Campus (Botley et al, 2005). This new project has increased this total to over 356,000 words of digital text, and has collected essays from three different institutions in order to further expand and enrich the corpus.